2012
DOI: 10.1016/j.juro.2012.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Lower Urinary Tract Symptoms from Childhood to Adulthood: A Population Based Study of 594 Finnish Individuals 4 to 26 Years Old

Abstract: Bladder control and urinary function exhibit considerable variation with age and gender. Due to the imperfections in bladder control in the general population, the evaluation of urinary tract disorders and outcomes of surgery in children and adolescents should be conducted with reference to control data according to age and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 25 publications
5
49
3
Order By: Relevance
“…There are inconsistencies in the paediatric literature with respect to gender differences in voiding symptoms. Kyrklund et al 10 found more voiding symptoms in boys than girls only in the age-group of 4 to 7 years, while such difference was not noted by others. 8,24 Psychotropic substance use increased the risk of LUTS in our adolescents.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…There are inconsistencies in the paediatric literature with respect to gender differences in voiding symptoms. Kyrklund et al 10 found more voiding symptoms in boys than girls only in the age-group of 4 to 7 years, while such difference was not noted by others. 8,24 Psychotropic substance use increased the risk of LUTS in our adolescents.…”
Section: Discussionmentioning
confidence: 79%
“…In children, the prevalence of LUTS peaks at age 5 to 7 years and then declines with increasing age up to 13 to 14 years. [7][8][9][10]20 The decline in prevalence has been attributed to the maturation of urinary bladder function along with the growth and development of children. Our study is the first to provide evidence that LUTS prevalence rises from the trough at the onset of adolescence and continues to increase throughout adolescence into adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,[28][29][30] Inclusion of healthy matched controls representing a normal population is extremely valuable, when health outcomes of a neonatal surgical disorder are assessed. 9,31 Otherwise, meaningful interpretation of the obtained results is much more difficult, because normality is not necessarily as straightforward as we think. For example 35% of healthy children and adolescents aged 4-26 years report fecal staining of underwear.…”
Section: Cross-sectional and Prospective Follow-up Studiesmentioning
confidence: 90%